THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND HUMAN CAPITAL LEADERSHIP ON EMPLOYEE PERFORMANCE - Suryanto Sosrowidigdo (Kusuma Negara Business School, 2020)
The purpose of this study was to determine and analyze the Transformational Leadership Style and Human Capital both partially and simultaneously the Employee Performance. This research was conducted at PT Trust Anugerah Persada with 55 employees as sample and the collected data is processed by multiple regression with SPSS version 23. This Research results showed that transformational leadership, positive and significant impact on Employee Performance, Human Capital positive and significant impact on Employee Performance, Transformational Leadership and Human Capital simultaneously positive and significant impact on Employee Performance.